Web-based resources in enhancing listening comprehension skills: a case study - Abu Baha, Osama; Mat Daud, Nuraihan (Kulliyyah of Languages and Management (KLM), International Islamic University Malaysia (IIUM), 2016)
Nowadays, technology plays an integrated role in improving the English skills and other life skills in almost all subjects. Many teachers can use their ICT skills to the maximum efficacy to fulfill the needs of the students who can be called ‘digital natives’ (Prenski, 2001). Teachers should be familiar with the technology as it save them time and effort as well. This paper aims at exploring how valuable the use of web-based resources can be in the English lectures especially in enhancing the listening skills. Moreover, this study aims at measuring the students’ achievement after a 4-month intervention. The study was conducted at University College of Educational Sciences-Palestine. The target group, 38 students, was the second year ESL Majors. ESL Labs, achievement test, and three interviews were the tools of the study. (MTUAS) Media and Technology Usage and Attitudes Scale Questionnaire was used to measure the students’ attitudes towards technology. All in all, web-based tools and resources are considered a challenge for teachers and students. The results of the research show that web-based resources have made dramatic improvement in listening comprehension skills. These resources can facilitate both teaching/learning process and the practices to a great extent.